2017
DOI: 10.1080/10253890.2017.1402883
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent environmental enrichment prevents behavioral and physiological sequelae of adolescent chronic stress in female (but not male) rats

Abstract: The late adolescent period is characterized by marked neurodevelopmental and endocrine fluctuations in the transition to early adulthood. Adolescents are highly responsive to the external environment, which enhances their ability to adapt and recover from challenges when given nurturing influences, but also makes them vulnerable to aberrant development when exposed to prolonged adverse situations. Female rats are particularly sensitive to the effects of chronic stress in adolescence, which manifests as passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
1
33
2
1
Order By: Relevance
“…In the present study, performance in the open field test was not affected in females. These data contrast somewhat a prior study from our group (Smith et al, 2018). This discrepancy may relate to the CVS protocol used: in the present work, animals did not receive periodic overnight isolation or crowding, which may constitute a more profound stress exposure for females (Note that this was done to avoid stressing the animals outside the range of bioavailability of CORT108297).…”
Section: Emotional Reactivity In the Open Field Test And Coping In Thcontrasting
confidence: 71%
See 1 more Smart Citation
“…In the present study, performance in the open field test was not affected in females. These data contrast somewhat a prior study from our group (Smith et al, 2018). This discrepancy may relate to the CVS protocol used: in the present work, animals did not receive periodic overnight isolation or crowding, which may constitute a more profound stress exposure for females (Note that this was done to avoid stressing the animals outside the range of bioavailability of CORT108297).…”
Section: Emotional Reactivity In the Open Field Test And Coping In Thcontrasting
confidence: 71%
“…Exposure to adolescent CVS does not affect the magnitude of the male HPA axis responses to an acute novel stressor in adulthood (5 weeks later) (Cotella et al, 2019;Smith et al, 2018).…”
Section: Hpa Axis Regulationmentioning
confidence: 95%
“…First, Sophie Walker and Carmen Sandi present findings highlighting the importance of how stress during relevant developmental time windowsin this case, adolescence and pubertyshape adult aggression and social behavior in concert with genetic predispositions for high or low HPA axis reactivity (Walker & Sandi, 2018). Along the same line, Brittany Smith, Jim Herman, and colleagues report that adolescent environmental enrichment prevents behavioral and physiological consequences of adolescent chronic stress exposure specifically in female rats, highlighting the importance of gender and studying sex-specific differences in stress (patho)physiology (Smith et al, 2017). Further, Oliver Sturman, Pierre-Luc Germain, and Johannes Bohacek emphasize the importance of including all possible measures from the behavioral repertoire of test animals in the analysis, as they often carry important information about the animal and the impact of stress exposure.…”
Section: Stress At Its Best: the 1st Munich Winter Conference On Stressmentioning
confidence: 53%
“…The forced swim test is commonly used to assess coping behavior (Molendijk & de Kloet, 2019); furthermore, antidepressants increase active coping and reduce immobility (Smith et al, 2017(Smith et al, , 2018Solomon et al, 2014). A modified test was used that involves a single swim exposure (Cryan et al, 2005), which differs from the original Porsolt forced swim test that requires repeated exposure to examine learned helplessness (Porsolt et al, 1977).…”
Section: Forced Swim Testmentioning
confidence: 99%
“…Although, recent studies have demonstrated that chronic stress-induced morphological changes in mPFC pyramidal neurons are similar in male and female rats (Anderson et al, 2019) and that homotypic chronic stress does not affect mPFC ∆ FosB expression differentially by sex (Bollinger et al, 2019). However, more widespread frontal lobe changes are sexually-divergent (Carvalho-Netto et al, 2011;Moench et al, 2019) and the behavioral consequences of chronic stress vary by sex (Borrow et al, 2018;Smith et al, 2018). Thus, future studies examining females would provide a better representation of the neural and behavioral consequences of chronic stress.…”
mentioning
confidence: 99%